Sekularisme dan Hak-Hak Individu dalam Usaha Melawan Diskriminasi Rasial dan Etnis di Indonesia - Jana C. Hertz (Antropologi Indonesia, 2003)
This article, based on original ethnographic research in two Indonesian non-government organizations, examines challenges faced by Indonesian activists in their work to improve inter-religious and inter-ethnic relations. The results of the research conclude that religiopolitical power struggles at the national level are the major obstacles for the NGO's observed in their efforts to promote legal justice for religious and ethnic minorities. In particular, the use of religion as a political identity in Indonesia raises sensitive issues related to secularism and individual rights. The article recommends that Indonesian NGO's focus their efforts on three main areas in their work to promote religious and ethnic justice: 1) clarifying the origins of secularism, in particular the perception that human rights are not a part of Indonesian culture; 2) discussion of the history of colonialism and imperialism and the connection to human rights; and 3) expanding the discourse on religion and its relationship to racial and ethnic discrimination, Islamic law, and national law.